Neurofinance Perspective on Traditional and Behavioral Finance in Accounting Students' Decisions - Frischa Faradilla Arwinda Mongan; Muliani Mangngalla; Ni Nyoman Ayu Suryandari; Desi Ratnasari; Alfianti Arung Badeng (Penerbit Goodwood, 2026)
Purpose: This study investigates the impact of traditional finance and behavioral finance on accounting students' financial decisions. A key objective is to emphasize the roles of financial literacy and psychological biases, and to determine whether neurofinance moderates their influence on individual choices. Methodology/approach: Adopting a quantitative design, data were gathered through questionnaires distributed to accounting students at UKI Paulus and UNMAS Denpasar. The research model was analyzed using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) technique, which enables testing of both direct and moderating relationships among complex variables. Results/findings: Both traditional finance and behavioral finance significantly influence students' financial decisions. Crucially, however, neurofinance does not significantly moderate the link between behavioral finance and financial decisions, suggesting that behavioral factors remain dominant. Future research should aim to integrate all three approaches into a unified framework. Conclusions: This study finds that behavioral finance has a more substantial impact on students' financial decisions than traditional finance. Neurofinance offers insights but does not significantly moderate this relationship, suggesting the need for further integration of all three approaches. Limitations: This research is confined to accounting students from two universities, which may limit the applicability of the results. Contribution: The study provides a unified framework for traditional, behavioral, and neurofinance. It uniquely shows that neurofinance moderates the impact of traditional finance, but not behavioral finance, providing new insights into student financial actions.